Definições curriculares em tempos de reformas educacionais: palavras-chave de uma História da Escola Primária no Paraná (1901 – 1930). - Sidmar dos Santos Meurer (2019)
The research aims to understand the interaction between educational and curricular reforms, analyzing the implications and consequences of initiatives that intended to reform primary school in Paraná, taken into action during the first three decades of the 20th century. By limiting the object of analysis around the production of “curriculum definitions”, the research examines the creation of legitimating discourses and analyses change patterns and permanences in the curriculum of primary school in Paraná during the period. The time limits were established by two events: 1901, the year which an important curriculum document was put into action, it intended to promote the first reform initiatives which introduced the school groups in the state; and 1930, when a broad project proposing an organic reform of the education in Paraná was suppressed while under process in the Legislative Chamber, a result of the national political scenario. Inspired by the perspective proposed by Ivor Goodson (1995, 1997, 2001) who advocates a production of a social history of the curriculum, the research questions: the curricular dynamics established aiming to capture how the curriculum documents related to each other, were impacted and treated the theoretical programs which guided the educational field in that moment; and how this was articulated with the expectations of carrying on issues arising from school practice in a scenario surrounded by attempts to reform school. To do so, we were methodologically inspired by the way Raymond Williams uses “key words” (2007) and thus analyze how the dynamics established by curriculum texts captured, treated, and proposed paths to some frequent and relevant notions in the educational debate, which were mobilized to create legitimating discourses and which became structuring principles of the curriculum in that time frame: active/activity, discipline, useful/usefulness. Aiming to capture the selective role of school curriculum in terms of demands and social and cultural priorities, we confronted, on one hand, the curriculum documents to the set of voices, demands and subjects interested in taking part of Paraná’s school reform and, on the other, the experiences of appropriation of those who were the main audience of curricular texts: the teachers. We used as sources a wide range of documents: normative documents and curricular texts; reports of political and educational authorities; pedagogical press; minutes and thesis of congresses and educational conferences; pedagogical compendia produced by people from Paraná or that circulated in the state; and teachers’ reports, letters, and requirements.